SIRT6 polymorphism rs117385980 is associated with longevity and healthy aging in Finnish men - Hirvonen, Katariina; Laivuori, Hannele; Lahti, Jari; Strandberg, Timo; Eriksson, Johan G.; Hackman, Peter (BMC medical genetics, 2017)
Sirtuin-6 (SIRT6) is involved in various crucial cellular pathways, being a key regulator of telomere structure, DNA repair, metabolism, transcriptional control and the NF-kappa B pathway. Sirt6 knock-out mice have been reported to develop typical features of aging and senescence at the age of 2-3 weeks and die within 4 weeks. The aim of this study was to investigate whether sequence variations of SIRT6 are associated with aging and longevity in Finnish men. The sample of this study consisted of 43 longer-living and healthy males and 92 male control subjects who have died of natural causes at an average age of 66,6 (±4,1) years and who belonged to the Helsinki Birth Cohort Study (HBCS). Single nucleotide polymorphisms (SNPs) in the exons and their surroundings of the SIRT6 were studied using direct PCR sequencing. The SNP rs117385980 (C > T), situated 23 bases downstream of the exon 2 exon/intron border was found in heterozygous form in 1/43 longer-living healthy men (Minor allele frequency (MAF) 0,0116) and in 9/92 controls (MAF 0,0489). To replicate this finding, we studied a group of 63 healthy men at an average age of 83 years from the Helsinki Businessmen Study (HBS)-cohort. The heterozygosity of the same SNP was seen in 2/63 men from the HBS-cohort (MAF 0,0159). Fisher exact test was performed in our two combined study samples. The P-value for all samples combined was 0.07 and the odds ratio 3.53 (95% confidence interval 0.96-13.4). These results suggest an inverse association between the T allele of rs117385980 and longevity. The result needs to be confirmed in a larger study. It remains to be determined whether rs117385980 itself has an effect or if it is a mere genetic marker for some other yet undiscovered sequence variant causing a functional effect.